Visualization of solving problems with sequences of numbers: Statistical comparison of the two methods - Mihajlov-Carević Miroslava; Milojević Nataša; Rešić Sead (Trendovi u Poslovanju)
The twenty-first century has brought the growing use of information and communication technologies in many spheres of human life. Also in education. In the learning process, students are increasingly focused on the use of modern technologies and software packages. Exploring the quality of maths teaching in primary school, we found students' knowledge of using modern technologies but also the lack of visual-logical approach in solving mathematical problems. In this paper, we show how the establishment of figurative numbers and selected examples that demonstrate the observation of legality, can direct students to a visual-logical approach to solving tasks with sets of numbers. We organized a three-hour exercise in experimental and control group, during which the experimental group was working with figurative numbers and the control group with selected examples. On the pre-test both groups showed a low degree of ability to observe legality among the numbers. On the post-test, both groups achieved progress compared to the pre-test, although the experimental group achieved greater progress. The research has shown that dealing with figurative numbers and selected examples that demonstrate the observation of legality, contributes to the development of pupils' abilities to perceive the laws of numbers and to apply the laws observed to solving problems with sets and arrays of numbers.